PERAN GURU AL-QUR’AN HADITS DALAM PENINGKATAN KEMAMPUAN MEMBACA AL-QUR’AN (Studi Kasus SMA Muhammadiyah Tanah Grogot Kab. Paser) - Rahim, Abdan; Al Barauwi, Rahmadhani; Khairunnisa, Siti Lathifah (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2024)
The background of the problem in this research highlights issues or challenges that have led to outcomes that are not as expected. Among the obstacles identified is the lack of students’ understanding in reading the Qur’an, both in terms of makhrajul huruf (pronunciation of letters) and the application of tajwid (rules of Qur’anic recitation). Therefore, this research aims to examine the role of Qur’an Hadith teachers in improving students’ ability to read the Qur’an at SMA Muhammadiyah. This study is a field research employing a qualitative descriptive approach. The research was conducted at SMA Muhammadiyah Tanah Grogot. The subjects of the study are Qur’an Hadith teachers at SMA Muhammadiyah, while the object of the research is the role of these teachers in enhancing the students' Qur’anic reading skills. The data collection techniques used in this research include observation, interviews, and documentation. Based on the results of the study, it can be concluded that the role of Qur’an Hadith teachers in improving students' ability to read the Qur’an at SMA Muhammadiyah has been very effective. The teachers fulfill their roles as instructors, mentors, evaluators, and culminators, achieving significant success in enhancing the Qur’anic reading abilities of the students at SMA Muhammadiyah.